Decentralized Decision-Making in Global Trade: Cybernetic Governance Through Logistic Informatics - Mirzayev, Natig (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This article explores the integration of cybernetic principles and informatics in shaping decentralised decision-making mechanisms in global trade logistics. In an era marked by increasing complexity, supply chain disruptions, and rapidly evolving technological landscapes, traditional centralised logistics systems often struggle to adapt efficiently. To address these challenges, the study emphasises systemic adaptability, autonomous feedback control, and digital governance as foundational components for the future of trade logistics. It introduces a cyber-informatic framework that leverages real-time data processing, self-regulating algorithms, and networked decision nodes to enhance the resilience, transparency, and efficiency of trade operations across borders. Drawing from comparative analyses of centralised versus decentralised logistics models, the paper demonstrates that distributed control systems – rooted in cybernetic theory – can more effectively respond to external shocks, reduce latency in decision-making, and enable more flexible resource allocation. Case studies from sectors such as maritime shipping, smart warehousing, and cross-border e-commerce illustrate the practical advantages of cyber-informatic architectures in mitigating risks and maintaining operational continuity under uncertainty. Furthermore, the framework supports the transition toward digital trade governance by aligning with emerging global standards for data interoperability, autonomous compliance, and AI-assisted policy execution. The study offers theoretical and applied insights for policymakers, technologists, and supply chain managers seeking to modernise logistics infrastructure while navigating an increasingly decentralised and digitised global economy. By advancing a cyber-informatics approach to logistics, it contributes to the evolving discourse on sustainable, adaptive, and intelligent trade systems.